Geographic tongue in 8-month-old monozygotic twins: Case report with review of literature - Saru Thakur; Mudita Gupta; G R Tegta; Kuldeep Verma (Wolters Kluwer Medknow Publications, 2018)
Geographical tongue is a benign inflammatory disorder of the tongue characterized by map like areas of erythema which are not constant in size, shape, or location. Positive family history may be reported in few cases, but so far there is a single case report of geographical tongue in monozygotic twins 5-year-old. We report a case of geographical tongue in monozygotic twins in infants 8-month-old, which is the first case in twins in infancy to the best of our knowledge.